2014
DOI: 10.1371/journal.pone.0107735
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Regional Cerebral Blood Flow in Depression Using 320-Slice Computed Tomography

Abstract: While there is evidence that the development and course of major depressive disorder (MDD) symptomatology is associated with vascular disease, and that there are changes in energy utilization in the disorder, the extent to which cerebral blood flow is changed in this condition is not clear. This study utilized a novel imaging technique previously used in coronary and stroke patients, 320-slice Computed-Tomography (CT), to assess regional cerebral blood flow (rCBF) in those with MDD and examine the pattern of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…For example, a study using 320-Slice Computed Tomography found that the rCBF of the left hemisphere is lower than that in the right hemisphere in depression patients (14), although the present study did not find that rCBF increased in the right hemisphere in depression patients compared with the healthy control subjects. Additionally, numerous electrophysiology studies confirmed that brain electrical activity also exhibits an asymmetric pattern.…”
Section: Discussioncontrasting
confidence: 95%
“…For example, a study using 320-Slice Computed Tomography found that the rCBF of the left hemisphere is lower than that in the right hemisphere in depression patients (14), although the present study did not find that rCBF increased in the right hemisphere in depression patients compared with the healthy control subjects. Additionally, numerous electrophysiology studies confirmed that brain electrical activity also exhibits an asymmetric pattern.…”
Section: Discussioncontrasting
confidence: 95%
“…The specific alteration in the patients with a family history was the increased rCBF in the bilateral basal ganglia, the bilateral middle temporal gyrus, the lateral inferior gyrus, the left paracentral gyrus, the right thalamus, these findings supported the hypothesis that increased cerebellar-default-mode-network connectivity in MDD patients to some extent [ 27 ]. Previous studies confirmed that functional or structural alterations in the prefrontal-limbic system participated in the regulation of affection, the regulation of memory processes and executive function [ 7 , 28 31 ]. Previous studies have also reported that decreased rCBF was also found in the prefrontal cortex and the orbital prefrontal cortex and that these brain regions participated in the regulation of aggression, sexual functioning and perseverative affection processing [ 23 , 31 33 ].…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies confirmed that functional or structural alterations in the prefrontal-limbic system participated in the regulation of affection, the regulation of memory processes and executive function [ 7 , 28 31 ]. Previous studies have also reported that decreased rCBF was also found in the prefrontal cortex and the orbital prefrontal cortex and that these brain regions participated in the regulation of aggression, sexual functioning and perseverative affection processing [ 23 , 31 33 ]. In addition, decreased rCBF in the insular in our present study supported the hypothesis that insular act as an integration center of emotional processing which is disrupted in the depressed patients [ 34 ].…”
Section: Discussionmentioning
confidence: 75%
“…A lot of brain imaging studies for patients with depression have reported blood flow changes in various portions of the brain . However, these results were not necessarily consistent, partly due to the heterogeneity in depression.…”
Section: Discussionmentioning
confidence: 92%
“…A lot of brain imaging studies for patients with depression have reported blood flow changes in various portions of the brain. 17,18 However, these results were not necessarily consistent, partly due to the heterogeneity in depression. Among them, asymmetry in grey matter volume reduction or cerebral blood flow between bilateral hemispheres has been reported.…”
Section: Pbs Symptom Laterality and Depressive Historymentioning
confidence: 87%